RUMAH TERAPI ADIKSI VIDEO GAME DI BANJARBARU - Adha, Muhammad Adjar; Sarbini, Gusti Novi; Huzairin, Muhammad Deddy (UNIVERSITAS LAMBUNG MANGKURAT, 2024)
Addiction can affect both physically and psychologically, causing personality problems and behavioral changes in the social environment. Special facilities are needed that have a planned recovery program, handling dependencies that do not have a planned recovery program will have further impacts. Therapeutic houses must pay attention to the comfort and safety of its users which can help restore the sufferer's physical and psychological condition. The environment influences the recovery process. By using environmental healing methods, the three approaches used combine natural, sensory and psychological elements. Elements of nature can be felt through the five senses. The senses can help see, hear and feel the natural beauty that is designed. This affects the psychology of the patient. Psychologically, patients will feel comfortable and safe within themselves.